Pytochemical screening and evaluation antimicrobial activity of the methanol extract of Ficus carica - Hakima, Belattar; Himour, Sara; Yahia, Abdelouahab (Revista Mexicana de Ciencias Agrícolas, 2021)
Fig tree (Ficus carica Linn.) was appreciated as food and for its medicinal properties, it grows in Mediterranean region, and it is admirably adapted to the conditions of Algeria. The use of natural resources to treat and cure diseases is an old and still widespread method. The objective of this work was to evaluate the antibacterial activity that exists through methanolic extracts of fig leaves grown in the Algerian environment. Antibacterial assay was carried out via disc diffusion method to measure the diameter of the zone of inhibition on the Müller-Hinton agar plate against four selected bacteria strains Staphylococcus aureus (Gram positive) and Pseudomonas aeruginosa, Escherichia coli, klebsiella pneumonia (Gram negative), in addition to the detection of some active compounds was carried out by phychemical screening. The result obtained showed that F. carica extracts revealed the presence of flavonoids, saponins, tannin, alkaloids. The presence of secondary metabolites made in these extracts is the cause of the observed antimicrobial potential. Consequently, all extracts exhibited the bactericidal effect towards the bacteria tested, while the crude extract of methanol was active against Gram positive bacteria more than Gram negative bacteria. In this study, the potential for development of alternative antibiotics derived from the methalonic extract of fig leaves was highlighted.